Biographie et autobiographie dans le Livre du Courtisan de Baldassare Castiglione - Guillaume Alonge (L'Atelier du CRH, 2019)
The article focuses on a reflection on the concept of collective biography, resonated with another term, the term of generation. These two concepts can be useful tools for the historian, particularly with regard to certain historical moments of passage. The concrete case from which the reflection develops is that of the generation of the Courtisan, the generation of those men, aristocrats and gentlemen of Italy at the beginning of the Sixteenth Century who were confronted with the dramas of the Italian wars and the collapse of the small states of the peninsula. Baldassar Castiglione chose several of these men as characters in his best-known work, The Book of the Courtier. In this case, therefore, the generational consciousness of the actors and the self-representation of the generation is done through a literary text. A text that is configured as the experience of an autobiography which is not only an individual one, but a collective one as well. It is striking to note that the Courtier has a very long genesis, with several versions, several elaborations. It was not until 20 years after he began to write that Castiglione decided –moreover because of constraints beyond his will– to publish it. It is interesting to note that some historical characters, described in the book, took part in the editorial development, and then the promotion of the work across all the courts of Europe. In recent decades, the story of the reception of the Courtier and the use of the text from the European readers of Modern Age ended up hiding what the Courtier meant for its author and for the men of the time: the work meant to be above all a generational representation, and a political and cultural instrument at the service of a strategy of social self-promotion